Implementing a coastal dune vulnerability index (CDVI) to support coastal management in different settings (Brazil and Italy). (1st October 2019) - Bertoni, Duccio; Sarti, Giovanni; Alquini, Fernanda; Ciccarelli, Daniela
Abstract: In this paper, the vulnerability of two dune fields located in southern Brazil (São Francisco do Sul Island) and western Italy (Tuscany) has been defined through the implementation of a Coastal Dune Vulnerability Index (CDVI). As the sites belonged to settings characterized by huge differences in terms of physical processes (Atlantic Ocean and Mediterranean Sea), the index has been adapted accordingly to minimize the influence of the dissimilarities in an attempt to define potential vulnerability parameters they might have in common. Five main groups of factors were taken into account in the design of the index: Geomorphological Condition of the Dune system (GCD), Marine Influence (MI), Aeolian Effect (AE), Vegetation Condition (VC), and Human Effect (HE) for a total of 51 variables. A total vulnerability index was calculated for each site. Cluster analysis and non-metric multidimensional scaling identified two main groups characterized by medium values of vulnerability (0.32–0.49): as a result, the vulnerability of both sites can be defined as "medium". In more detail, GCD turned out to be the most influent factor on both settings; subordinately, marine influence also resulted relevant on the Oceanic site. The CDVI proved to be a flexible tool, as it was easily adjusted to work on such different sites. In this sense it will be of great support to increase the awareness of coastal managers and decision makers about the mutual interactions of many factors and processes that contribute to the evolution of coastal dunes regardless of the geographical setting. Highlights: Dune vulnerability index can be easily adjusted to be used on different settings. Geomorphologic factors exert major influence at the Atlantic and Mediterranean sites. Marine influence is particularly high at the Atlantic site. Increasing the resilience of dune systems should lead to weaken GDC vulnerability. Vulnerability indices are a useful tool to support coastal management.